2002
DOI: 10.1063/1.1495883
|View full text |Cite
|
Sign up to set email alerts
|

Current-controlled bi-stable domain configurations in Ni81Fe19 elements: An approach to magnetic memory devices

Abstract: The discovery of current-switchable bi-stable remanent domain configurations on small ferromagnetic islands is reported. Rectangular NiFe islands with a thickness of 50 to 100 nm and lateral dimensions on the order of several microns were imaged using magnetic force microscopy after application of 10 ns current pulses through the material. The closure configuration can be set into either the 4 or 7 domain configuration by applying positive or negative current polarity at density on the order 10 7 A/cm 2 . The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 13 publications
5
44
0
Order By: Relevance
“…In this paper, we focus our discussions on two effects: domain wall dynamics and magnetization instability. Recently, both topics have received considerably interests in experiments [1,2,3,4,5,6,7,8,9,10,11] and in theories [12,13,14,15,16,17,18,19]. It is shown that the current is able to displace magnetic domain walls in a spin valve [3], in a constricted nanowire [4], in U-shaped (or L-shaped) nanowires [5,6], in a ring structure [7] and in zigzag wires [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we focus our discussions on two effects: domain wall dynamics and magnetization instability. Recently, both topics have received considerably interests in experiments [1,2,3,4,5,6,7,8,9,10,11] and in theories [12,13,14,15,16,17,18,19]. It is shown that the current is able to displace magnetic domain walls in a spin valve [3], in a constricted nanowire [4], in U-shaped (or L-shaped) nanowires [5,6], in a ring structure [7] and in zigzag wires [8].…”
Section: Introductionmentioning
confidence: 99%
“…7,21,23,24,25 While it has been originally suggested that the discrepancy could be due to thermal activation 11,25,26,27,28 or surface roughness 25 , it has recently been found that the domain-wall velocity depends on the type of the domain wall 26,29 which can be changed by a spin-polarized current. 8,26,30,31 Recently it has been observed that the velocity of field-driven domain-wall motion 32 can be altered by ± 100 m/s by a pulsed spinpolarized current 33 and that the motion can even be halted completely. 34 It is now assumed that the adiabatic term is largely responsible for the acceleration of the domain wall while the non-adiabatic term will cause the wall to continually move.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4,5,6,7,8,9,10 Most theories ascribe this behavior to the interplay between spin-transfer (the quantum mechanical transfer of spin angular momentum between conduction electrons and the sample magnetization) and magnetization damping of the Gilbert type. 11 Contrary to the second point, we argue in this paper that LandauLifshitz damping 12 provides the most natural description of the dynamics.…”
Section: Introductionmentioning
confidence: 99%